Investigation of mechanical properties and corrosion behavior of Nickel Bronze alloy prepared powder metallurgy. (2023) - Veerappan, G.; Pritima, D.; Marichamy, S.; Dhinakaran, V.; Sathish, S.
Abstract: In this Experimental investigation, Nickel Bronze alloy was prepared using powder metallurgy route. Three different percentages of nickel (2 wt%, 4 wt% and 6 wt%) are mixed in bronze matrix. A 250KN hydraulic press is used to compact the ball milled powders and the compacted specimens are sintered at two different sintering temperatures such as 800 °C and 900 °C.The sintered specimens were tested for compression strength, hardness and corrosion. 4 wt% Ni –Bronze exhibits high compression strength of MPa. 6 wt% Ni- Bronze exhibits high hardness as well as better corrosion resistant.. 4 wt% Ni –Bronze exhibits high sinterability of 0.78 % among other specimens.